(3GdCOdI GdTQjaI Ydi ePgH GdEeGe CHj MfjaIs - (3CMeO Hf YHO Gddg Hf CHj HcQ Hf GdbGSe Hf eMeO GdaQGejSs ((3SYO Hf eMeO GdOjQi GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd TjNfG eMeO Hf YHO Gddg GdOjQi GdMfai LeYJ eSGFd ai GdNdGajGJ QOkG Ydi ef RYe Cf CHG MfjaI QMeg Gddg bOe GdbjGS Ydi GdNHQ hPcQJ ePGgH GdYdeGA ai Pdc s
(3BNQgG (B:s
(3PcQg ai LhGeY ddabg bGd ai GdHOGFY hGdeMjW hgh Chab GdQhGjGJ Yfg GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdeNWhW cJH HNWjf eNJdajf hdcf CZdHg cJH HNW fSN Lejd heTchd hjHO Cf GdeNWhW fSN LRA efg GHf GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(897) s
Keywords: (3Gdabg GdMfajs